Twenty-Year Analysis of Surfing Head and Neck Injuries Presenting to United States Emergency Departments Showed a Decrease in Overall Injuries Despite Steady Concussion Rates - Eli M. Snyder, B.S.; Elizabeth A. Rooks, B.A.; Kyle K. Obana, M.D.; Spencer K.Y. Chang, M.D.; Christopher S. Ahmad, M.D.; Charles A. Popkin, M.D.; David P. Trofa, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To analyze the etiology, diagnosis, and incidence of head and neck (HN) injuries among ocean surfers. Methods: The National Electronic Injury Surveillance System database was queried for surfing HN injuries presenting to United States emergency departments (EDs) between January 2003 and December 2022. Date of presentation, age, sex, race, injured body part, injury diagnosis, and disposition, as well as a brief injury narrative, were included in the data. National estimates (NEs) were calculated using the associated statistical weight of the reporting hospital. Results: A total of 1,359 surfing-related HN injuries (NE, 90,872) were included in this study. The average age at presentation was 29.2 ± 13.8 years (range, 3 to 81 years). The most commonly specified mechanisms of injury were impact with board (NE, 48,360 [53%]) and impact with ocean floor (NE, 8,690 [10%]). Concussions represented 5% of surfing HN injuries and occurred at a higher rate (8%) in the age group younger than 20 years. There were statistically significant decreases in overall HN injuries (P < .01) (coefficient, –270; 95% confidence interval [CI], –355 to –206), lacerations (P < .01) (coefficient, –208; 95% CI, –258 to –158), and impact-with-board injuries (P < .01) (coefficient, –177; 95% CI, –327 to –117) presenting to United States EDs from 2003 to 2022. Conclusions: Although surfing HN injury ED presentations decreased from 2003 to 2022, the rate of surfing-related concussions presenting to EDs remained steady. Concussions therefore remain a significant concern in surfing, especially among surfers under 20 years of age. Clinical Relevance: As the sport of surfing has increased in popularity, it is important to understand the range of surfing injuries seen in EDs. HN injuries, especially concussions, should be thoroughly investigated to better understand the risks of ocean surfing, to advise athletes, and to develop effective injury prevention strategies.